2014
DOI: 10.1108/tqm-11-2012-0089
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of quality satisfaction between transactional and relational customers in e-commerce

Abstract: Purpose-The purpose of this paper is to examine quality satisfaction between transactional and relational customers in e-commerce, and it also explores the moderating effect of perceived control and perceived enjoyment on quality satisfaction. Design/methodology/approach-Multivariate analysis of variance and two-way ANOVA were conducted to test the study hypotheses. The samples include 470 university students in the northeastern USA to whom an online survey was administered. Findings-Results show that system q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In particular, scholars have investigated the impact of CSR disclosure on consumer's decision-making process (Pradhan, 2018). Accordingly, websites should be considered a proper communication channel to reach consumers (Hollebeek et al , 2007; Yen, 2014; Cobelli et al , 2021). More specifically, online disclosure should support companies in enhancing consumers' involvement in corporate social responsibility practices, influencing consumers' purchasing behaviour (Barber et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, scholars have investigated the impact of CSR disclosure on consumer's decision-making process (Pradhan, 2018). Accordingly, websites should be considered a proper communication channel to reach consumers (Hollebeek et al , 2007; Yen, 2014; Cobelli et al , 2021). More specifically, online disclosure should support companies in enhancing consumers' involvement in corporate social responsibility practices, influencing consumers' purchasing behaviour (Barber et al , 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, multiple touchpoints in a diversity of channels and media increase the complexity of the customer experience (CE), which holds a primary role in services literature (e.g. Yen, 2014;Lemon and Verhoef, 2016;McCrory et al, 2017). Homburg et al (2017, p. 8) describe CE as "the evolvement of a person's sensorial, affective, cognitive, relational, and behavioral 444 TQM 30,5 responses to a firm or brand by living through a journey of touchpoints along pre-purchase, purchase, and post-purchase situations."…”
Section: Introductionmentioning
confidence: 99%
“…Dai and Zhang (2020) have recently found that the use of, and satisfaction with e‐commerce platforms is influenced by the sensitivity of communication, and the effectiveness of B2C interrelation. Yen's (2014) study of consumer satisfaction with e‐commerce platforms revealed that the quality of information is more important for transaction and relational customers in communication. Yen's (2014) study found that quality information enhances security albeit with an insignificant P ‐value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yen's (2014) study of consumer satisfaction with e‐commerce platforms revealed that the quality of information is more important for transaction and relational customers in communication. Yen's (2014) study found that quality information enhances security albeit with an insignificant P ‐value. They found platform quality as a significant customer satisfier.…”
Section: Literature Reviewmentioning
confidence: 99%